2022
DOI: 10.1590/1413-81232022275.07502021
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk during heat waves in the summer 2013-2014 in 18 provinces of Argentina: Ecological study

Abstract: Increased frequency of heat waves (HWs) is one of the prominent consequences of climate change. Its impact on human health has been mostly reported in the northern hemisphere but has been poorly studied in the southern hemisphere. The aim of this study was to analyze the effects of the HWs waves occurred in the warm season 2013-14 on mortality in the center-north region of Argentina, where 22 million people live. It was carried out an observational study of ecological-type contrasting the mortality occurred du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Typically, people with pre-existing health conditions, those that are over 65 or under five, have low incomes, work indoors with poor ventilation in homes or factories, and outdoor workers are more vulnerable to heat stress, heat stroke, or death (Green et al 2019). In particular, previous studies considering some recent (2005-2015) heatwaves in Argentina, documented an increase in death risk for people over 60, particularly those older than 80, and individuals under 15 years of age (Chesini et al 2019(Chesini et al , 2022). An early warning system for heatwaves have been developed in Argentina by the SMN and became operative during the summer of 2018 (Herrera et al 2021).…”
Section: Vulnerability Exposure and Impactsmentioning
confidence: 96%
See 1 more Smart Citation
“…Typically, people with pre-existing health conditions, those that are over 65 or under five, have low incomes, work indoors with poor ventilation in homes or factories, and outdoor workers are more vulnerable to heat stress, heat stroke, or death (Green et al 2019). In particular, previous studies considering some recent (2005-2015) heatwaves in Argentina, documented an increase in death risk for people over 60, particularly those older than 80, and individuals under 15 years of age (Chesini et al 2019(Chesini et al , 2022). An early warning system for heatwaves have been developed in Argentina by the SMN and became operative during the summer of 2018 (Herrera et al 2021).…”
Section: Vulnerability Exposure and Impactsmentioning
confidence: 96%
“…An early warning system for heatwaves have been developed in Argentina by the SMN and became operative during the summer of 2018 (Herrera et al 2021). This system operates during the warm season (October to March) issuing daily alerts for 57 locations of the country, with the aim of enabling both the population and civil protection agencies to take appropriate prevention, mitigation and response measures at each alert level (Chesini et al 2022). If there is a heat risk alert (yellow, orange, or red) for the following 24 h, the Ministry of Security and the Ministry of Health are notified and the Ministry of Health will launch an epidemiological alert and make it public through social media, press agencies, and national media, with recommended actions to the general population and at-risk groups.…”
Section: Vulnerability Exposure and Impactsmentioning
confidence: 99%
“…In Latin America, one of the earliest multicountry studies [ 30 ] found a significant association between elevated temperatures and mortality in Santiago, São Paulo, and Mexico City, mostly among older people. Also, in Latin America, [ 31 ] investigated the effects on mortality of the HWs that occurred in the center-north region of Argentina during the warm season of 2013–2014. The authors observed increased death risk in 13 of the 18 provinces analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the heat waves that swept through England and Wales in the summer of 2022 reported an additional death toll of 3,271 people (ONS 2022). Figure 1 shows the heat wave related additional mortalities that occurred in the past decades in the United Kingdom (ONS 2022), France (Fouillet et al 2006;Hughes et al 2016), India and Pakistan (Hughes et al 2016), Japan (Hughes et al 2016), Australia (Hughes et al 2016), California in the United States (Hughes et al 2016; Edwards et al 2006), Germany (De Bono et al 2004), Spain (De Bono et al 2004), Italy (De Bono et al 2004), Argentina (Chesini et al 2022), and Senegal (Sy et al 2021). These mortality rates are representative numbers as these may have been calculated using different methods in different regions and may not be directly comparable.…”
Section: Introductionmentioning
confidence: 99%